Penguatan Literasi untuk Meningkatkan kemampuan Berbahasa Bali Siswa di SMP Cipta Dharma - Dwi Yanti, Meidita (UPADHYAYA: JURNAL PENELITIAN PENDIDIKAN, 2026)
Regional or local languages are languages that are passed down from generation to generation within a particular region of a sovereign country, such as an indigenous area, federal state, province, or territory. Regional languages function as a means of communication and serve as an important marker of regional identity. However, in the era of globalization, the Balinese language faces various challenges in its preservation, particularly due to the dominance of the national language and foreign languages in daily life. Recognizing this condition, the Government of Bali Province has established several policies to preserve the Balinese language, one of which is Regional Regulation Number 1 of 2018 concerning Balinese Language, Script, and Literature, as stated in Article 1. SMP Cipta Dharma is one of the private junior high schools in Bali. As a school located in Bali, SMP Cipta Dharma also plays a role in preserving the Balinese language by implementing various approaches in teaching Balinese as a subject. Therefore, it is important to examine how the curriculum is implemented and how Balinese language learning is carried out at the school. This study employs a qualitative research method, with interviews used as the data collection technique. The results of this study indicate that literacy strengthening is the main approach in Balinese language learning at SMP Cipta Dharma, supported by the use of various methods, strategies, and engaging learning media. This approach is considered effective in improving students’ understanding as well as their interest in learning the Balinese language.